Digestible lysine levels for brown layers - Souza, Henrique Baltazar de; Faria, Douglas Emygdio de; Caetano, Vinicius Camargo; Santos, Andréa Luciana dos; Araújo, Raquel Bighetti; Sakamoto, Márcia Izumi (Acta Scientiarum. Animal Sciences, 2014)
This study was carried out to evaluate the effects of different digestible dietary lysine levels on performance and egg quality characteristics, from 25 to 41 weeks of age. One hundred twenty Hy-Line Brown layers were randomly distributed in five treatments with six replications of four birds each, totaling 30 experimental units. Experimental diets were based on corn and soybean meal, were isocaloric and isonutrient, with differences only in lysine levels (0.70, 0.75, 0.80, 0.85, and 0.90%). The study evaluated feed intake, lysine intake, energy consumption, egg production, egg weight, egg mass, and feed conversion. Internal egg quality was evaluated by Haugh unit, the percentages of yolk and albumen percentage, while external quality was measured by specific gravity, eggshell thickness and shell percentage. It was concluded that the level of 0.70% of digestible lysine or the intake of 708 mg bird-1 day-1 for Hy-Line Brown layers from 25 to 41 weeks of age can be enough to express the genetic potential.